Use of antidepressants in women after prophylactic bilateral oophorectomy: A Danish national cohort study. Issue 4 (11th February 2020) - Abildgaard, Julie; Ahlström, Magnus Glindvad; Nielsen, Dorte Lisbeth; Daugaard, Gedske; Lindegaard, Birgitte; Obel, Niels; Lidegaard, Øjvind
Abstract: Objective: To investigate the association between prophylactic bilateral oophorectomy and use of antidepressants in women with a family history of cancer. Methods: Nationwide population‐based cohort study using Danish National Registries including women oophorectomized due to a family history of cancer (n = 2, 002) and an age matched reference group (n = 18, 018). Analyses were stratified by age at time of bilateral oophorectomy and use of hormone replacement therapy (HRT). Results: Women oophorectomized at age ≤ 45 years were more likely to use antidepressants from the first year after bilateral oophorectomy (OR = 1.34; 95 % CI: 1.08‐1.65) compared to the reference group. Women oophorectomized at age 46‐55 years and at age >55 years had no significantly increased use of antidepressants (OR = 0.90; 95 % CI: 0.68‐1.18 and OR = 1.14; 95 % CI: 0.81‐1.61). The increased use of antidepressants in women oophorectomized at age ≤ 45 years was limited to women treated with HRT (OR = 1.51; 95 % CI: 1.18‐1.94) whereas women oophorectomized at age ≤ 45 years not treated with HRT had no increased use of antidepressants (OR = 1.03; 95 % CI: 0.70‐1.51). Conclusions: Women oophorectomized due to a family history of cancer at age ≤ 45 years were more likely to use antidepressants after bilateral oophorectomy. The increased use of antidepressants was limited to women treated with HRT. The study calls for further large‐scale studies to understand how bilateral oophorectomy and concomitant HRT affects risk of depression in women with a family history of cancer.